Petroleum engineer's guide to oil field chemicals and fluids - Fink, Johannes Karl (Gulf Professional Pub, 2012)
The oil and gas engineer on the job requires knowing all the available oil field chemicals and fluid applications that are applicable to the operation. Updated with the newest technology and available products, Petroleum Engineer's Guide to Oil Field Chemicals and Fluids, Second Edition, delivers all the necessary lists of chemicals by use, their basic components, benefits, and environmental implications. In order to maintain reservoir protection and peak well production performance, operators demand to know all the options that are available. Instead of searching through various sources, Petroleum Engineer's Guide to Oil Field Chemicals and Fluids, Second Edition, presents a one-stop non-commercialized approach by organizing the products by function, matching the chemical to the process for practical problem-solving and extending the coverage with additional resources and supportive materials. Covering the full spectrum, including fluid loss additives, drilling muds, cement additives, and oil spill treating agents, this must-have reference answers to every oil and gas operation with more options for lower costs, safer use, and enhanced production.
Keywords: Oil field chemicals.; elektronické knihy; electronic books